Mass–spring–damper modeling and stability analysis of type-4 wind turbines connected into asymmetrical weak AC grid. (December 2020) - Xu, Hailiang; Wang, Shinan; Hu, Jiabing
Abstract: Nowadays, grid codes of various countries have required that grid-connected wind turbines should possess the capability of negative sequence current control during asymmetrical grid condition. As for type-4 wind turbines, however, due to the existence of the negative sequence voltage, the interaction between the dc-link voltage control (DVC) and phase locked loop (PLL) of the grid-side converter is likely to cause small-signal instability when the impedance of the AC grid cannot be ignored. As a specific contribution, the paper establishes a detailed four degree-of-freedom mass–spring–damper model considering the couplings between the positive and negative sequence subsystems based on the theory of mechanical vibration, so as to characterize the modal interaction between the DVC and PLL. The model can be used to evaluate the influence of factors such as negative sequence voltage, grid impedance and control parameters on the system stability. Simulation studies were finally performed to verify the correctness of the proposed model and the analysis.